OPTIMIZING THE ROLE OF MICROFINANCE AND SPECIALIZED FINANCIAL INSTITUTIONS IN PROMOTING FINANCIAL INCLUSION AND PRODUCTIVE FINANCING IN NORTH SUMATRA - Delima Afriyanti; Ahda Segati; Surya Tegar Widjiantoro; Nurlaili Janati; Rini Ariyanti (Ekonomi Islam, 2026)
Research aims: This study examines the roles of Lembaga Keuangan Khusus (LKK) and Lembaga Keuangan Mikro (LKM) in enhancing financial inclusion and productive financing in North Sumatra Province, Indonesia. Design/Methodology/Approach: This research employs a descriptive qualitative approach using secondary data from OJK, BPS, LPDB-KUMKM, and academic sources. The study evaluates LKK and LKM contributions to regional economic empowerment. Research Findings: Findings show that LKK, such as LPDB-KUMKM, support cooperatives and SMEs through revolving fund programs. Meanwhile, LKM, such as BWM and BMT, strengthen microfinance based on social and sharia principles. Although financial inclusion in North Sumatra has reached 77.24%, challenges related to literacy and digitalization still limit the optimal role of regional financial institutions. Theoretical Contribution/Originality: This study contributes to regional financial system literature by integrating the roles of LKK and LKM within inclusive and sharia finance. It highlights maqāṣid al-syarī’ah principles as a value foundation for building a fair and sustainable financial ecosystem. Practical/Policy Implications: This research recommends strengthening institutional synergy, accelerating digital transformation, and improving financial literacy programs to optimize the roles of LKK and LKM. Policymakers and practitioners are encouraged to adopt strategies aligned with local economic needs and sharia financial principles. Research Limitations/ Implications: This study relies on secondary data, limiting its ability to describe field conditions in depth. Future research should use primary data and empirical methods to obtain a comprehensive understanding of LKK and LKM effectiveness in regional financial development.